Sequence of telephone openings in the workplaces in a Kazakh community - Bekeyeva, Nuraisha; Kucherbayeva, Dina; Orazbayeva, Fauziya; Suleimenova, Zharkynbike (Opción, 2019)
The current study examines telephone conversation openings in the workplace in a Kazakh community via comparative qualitative research methods. The study shows that despite the fact that the core sequences of Schegloff’s model are present in the analyzed data, it could be argued that the Kazakh telephone discourse construction is culturally specific. In conclusion, each opening telephone conversation is dependent on factors, such as co-interactants’ age, gender, position at work and a type of relationship.